Identification of a novel anti-σ(E )factor in Neisseria meningitidis - Hopman, Carla Th P (BioMed Central, 2010)
BACKGROUND: Fine tuning expression of genes is a prerequisite for the strictly human pathogen Neisseria meningitidis to survive hostile growth conditions and establish disease. Many bacterial species respond to stress by using alternative σ factors which, in complex with RNA polymerase holoenzyme, recognize specific promoter determinants. σ(E), encoded by rpoE (NMB2144) in meningococci, is known to be essential in mounting responses to environmental challenges in many pathogens. Here we identified genes belonging to the σ(E )regulon of meningococci. RESULTS: We show that meningococcal σ(E )is part of the polycistronic operon NMB2140-NMB2145 and autoregulated. In addition we demonstrate that σ(E )controls expression of methionine sulfoxide reductase (MsrA/MsrB). Moreover, we provide evidence that the activity of σ(E )is under control of NMB2145, directly downstream of rpoE. The protein encoded by NMB2145 is structurally related to anti-sigma domain (ASD) proteins and characterized by a zinc containing anti-σ factor (ZAS) motif, a hall mark of a specific class of Zn(2+-)binding ASD proteins acting as anti-σ factors. We demonstrate that Cys residues in ZAS, as well as the Cys residue on position 4, are essential for anti-σ(E )activity of NMB2145, as found for a minority of members of the ZAS family that are predicted to act in the cytoplasm and responding to oxidative stimuli. However, exposure of cells to oxidative stimuli did not result in altered expression of σ(E). CONCLUSIONS: Together, our results demonstrate that meningococci express a functional transcriptionally autoregulated σ(E )factor, the activity of which is controlled by a novel meningococcal anti-σ factor belonging to the ZAS family.